Case Report: Assessing COVID-19 Transmission in Professional Volleyball in Germany, September to December 2020: An Epidemiological Study - Morath, Oliver; Barsch, Friedrich; Lazaro, Adhara; Huzly, Daniela; Deibert, Peter (Frontiers in Sports and Active Living, 2022)
INTRODUCTION The SARS-CoV-2 pandemic poses extraordinary challenges in all fields of daily life. The WHO recommended social distancing guidelines and person-to-person contact was strongly discouraged to contain transmission. Team-based sports were questioned and widely debated. However, there is a lack of available evidence on the risk of in-game SARS-CoV-2 transmission. We aim to derive new insights regarding the risk of SARS-CoV2 infection during team sports and provide current opinion on how to behave during training and competition. METHODS We report on six competitive male volleyball players (national level) of the same team who were infected with COVID-19. The mode of transmission and potential virus spreading within the team was investigated. The entire course of infection was documented by detailed medical history of the players and RT-PCR tests confirmed suspected infections. Serological testing was performed to establish the antibody status of the team. RESULTS The investigation did not show strong evidence of viral transmission within the team during sporting activities. Only two players with PCR-proven infection hat detectable antibodies in two antibody assays. CONCLUSION Private and social gatherings can spread infection into team sports. Clearly defined test strategies and strict adherence to standard COVID-19 hygiene guidelines during sports seasons cannot be overemphasized.